SPECIFICITY OF HORMONAL AND METABOLIC STATUS IN PRIMARY HYPOTHYROIDISM MEN - Krytskyy, T.I.; Pasyechko, N.V. (World of Medicine and Biology, 2018)
The purpose of this study was to compare hormonal, anthropometric and metabolic parameters in men with hypothyroidism. Totally 60 males with primary hypothyroidism were studied. It has been established that hypothyroidism is accompanied by an increase in serum concentrations of cholesterol and low density lipoprotein when compared with the control group (25 men without hypothyroidism) and indicating metabolic disturbance. Our results have been shown the significant effect of hypothyroidism on testosterone and follicle stimulating hormone (FSH) serum concentration, but not on luteinizing hormone and estradiol levels. Patients with hypothyroidism had lower circulating testosterone and higher FSH level in comparison with the control group. The reproductive hormone changed in men with hypothyroidism which can result in deleterious effects on sexual functions including erectile dysfunction, reduced libido and alteration in spermatogenesis.
Keywords: hypothyroidism; reproductive hormones; testosterone; metabolic status; men